2017
DOI: 10.12911/22998993/68214
|View full text |Cite
|
Sign up to set email alerts
|

Coal Micronization Studies in Vibrating Mill in Terms of Coal Water Slurry (Cws) Fuel Preparation

Abstract: The paper presents the results of coal milling tests in the aspect of slurry fuel preparation. The tests were carried out with the use of vibrating mill with a working chamber of 47.5 dm 3 . The influence of milling time, amount and composition of grinding aids on the degree of fineness and particle size distribution have been investigated. It was found that the efficiency of the grinding process (in this type of milling device) depends primarily on the milling time and the share of grinding aids and -to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In the production, ball and vibrating mills of dry or wet grinding are used for grinding coal. These are characterized by multi-stage processing and greater metal consumption [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the production, ball and vibrating mills of dry or wet grinding are used for grinding coal. These are characterized by multi-stage processing and greater metal consumption [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are also increasing efforts to use coal to produce a more ecological type of fuel. The production of coal-water slurry (CWS) fuel can be a good example of such attempts [5][6][7]. However, meeting such needs requires improved methods for efficient coal comminution [8][9][10][11] and for appropriate coal sorting-such that would depend on and allow for its future application [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tests performed as part of the defined research program demonstrated the usefulness of a vibrating mill in the micronization process of two types of coal fine [7], intended for the production of CWS fuel. They also confirmed a positive effect of the comminution degree of brittle materials on the shape of their particles under mechanical grinding in an electro-hydraulic mill [41].…”
Section: Introductionmentioning
confidence: 99%